Blockchain Technology Innovation in Transforming Digital Business Models: A Case Study in the Financial Industry - Aksenta, Almasari; Syachrul, Syachrul (Penelitian dan Pengembangan Ilmu, 2024)
Blockchain technology has emerged as a transformational innovation with significant implications for the financial sector, increasing transparency, security and operational efficiency. This research aims to explore how blockchain technology can change digital business models in the financial industry. Using the PRISMA method, the author conducted a systematic review of relevant literature. The research results show that blockchain adoption can streamline operational processes, reduce costs, and increase data security. The implications of this research include increasing trust and efficiency in financial services, as well as providing practical guidance for the implementation of blockchain technology in the industry.